If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 6 = 4w Reorder the terms: 6 + 3x = 4w Solving 6 + 3x = 4w Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 3x = -6 + 4w Combine like terms: 6 + -6 = 0 0 + 3x = -6 + 4w 3x = -6 + 4w Divide each side by '3'. x = -2 + 1.333333333w Simplifying x = -2 + 1.333333333w
| .2x=7-.6x | | 1-5x=-4-4x | | -11x+9-4x=2 | | y/4=15/6 | | 7s-5-7s+9= | | 10.9x+15.56=-9.1x+13.86 | | m+3-2=7 | | 10.9x+15.56=9.1x+13.86 | | 4x-22=3x+17 | | A=x+xtd | | 7s-5-7s+5= | | 15=5x+x+7 | | 1-3/4= | | 2xy=6 | | 5x-2x+8=29 | | c=10*1/2 | | 2x=10*1/2 | | y=3.25x+40 | | 2b+x=477 | | 7(-2.5)= | | 2(b-8)+2(b-8)+b=14 | | 9x^2-54x+84=0 | | 2x+1=10*1/2 | | 2(-4-7v)=3-5(3v+5) | | 14v^2-42=0 | | 16-3x=-52 | | 13a-9=4a+9 | | 16=3x-9x+22 | | 2x+7(4x+23)=34 | | -5+4-x-1= | | 3(1-2p)=-(p+7) | | x^2+25x+130=0 |